Preparation and Evaluation of Econazole Nitrate Polymeric Micelle Solution as an Eye Drop - Aljanabi, Ali Hameed; Athmar Dh. H. Al-Shohani (Iraqi Journal of Pharmaceutical Sciences, 2025)
Econazole nitrate, a chemically produced triazole drug, is utilized to manage fungal keratitis. It has potent antifungal properties against many species; the readily available formula exhibits inadequate corneal permeability, visual aberrations, excessive tearing, dilution of tears, and leakage via the nasolacrimal duct. This research aimed to develop a polymeric micellar delivery system for econazole nitrate utilizing Poloxamer 407 (Pluronic F127) and Poloxamer 188 (Pluronic F68), with the intention of enhancing its solubility in aqueous environments and improving its penetration through the cornea. First, critical micelle concentration of P407 and P188 was measured using Iodine UV-absorption spectroscopic method. Polymeric micelles loaded with econazole nitrate were prepared using the rotary evaporation process and evaluated for particle size, polydispersity index, zeta potential and entrapment efficiency. Formulations with promising results further evaluated for in vitro drug permeation using Franz diffusion cell. The cumulative drug permeation (CDP) percentage exhibited significant variation, ranging from 56% to 83.2%.The optimum formulation F8 containing 1:60 drug: polymer ratio was evaluated for antifungal activity and ex vivo permeation study. A statistically significant difference in the antifungal activity between the reference standard and F8 was observed. F8 demonstrated a 3.42-fold increase in ex vivo permeability through the goat ocular membrane compared to the econazole nitrate solution. Using econazole nitrate polymeric micelle as a drug delivery system is efficient and superior in overcoming ocular obstacles, and facilitating the appropriate administration of lipophilic medicines.